2003
DOI: 10.1128/jb.185.18.5627-5631.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Surface Motility in Bacillus subtilis Is Dependent on Extracellular Surfactin and Potassium Ion

Abstract: Motility on surfaces is an important mechanism for bacterial colonization of new environments. In this report, we describe detection of rapid surface motility in the wild-type Bacillus subtilis Marburg strain, but not in several B. subtilis 168 derivatives. Motility involved formation of rapidly spreading dendritic structures, followed by profuse surface colonies if sufficient potassium ion was present. Potassium ion stimulated surfactin secretion, and the role of surfactin in surface motility was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
155
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(167 citation statements)
references
References 26 publications
7
155
0
2
Order By: Relevance
“…The presence of both flagella and a detergent-like lipopeptide (surfactin), secreted by the bacteria and subject to regulation by quorum sensing in planktonic culture (Solomon et al, 1995), has also been implicated in swarming in this organism (Ohgiwari et al, 1992;Wakita et al, 1998). Some reports, however, have indicated that swarming can occur independently of either flagella or surfactin (Dixit et al, 2002;Kinsinger et al, 2003;Mendelson & Salhi, 1996). In our studies with the laboratory strain 168 (Trp 2 ), the bacteria, although SrfA 2 , still swarmed efficiently on LB agar, albeit less rapidly than strain 3610.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of both flagella and a detergent-like lipopeptide (surfactin), secreted by the bacteria and subject to regulation by quorum sensing in planktonic culture (Solomon et al, 1995), has also been implicated in swarming in this organism (Ohgiwari et al, 1992;Wakita et al, 1998). Some reports, however, have indicated that swarming can occur independently of either flagella or surfactin (Dixit et al, 2002;Kinsinger et al, 2003;Mendelson & Salhi, 1996). In our studies with the laboratory strain 168 (Trp 2 ), the bacteria, although SrfA 2 , still swarmed efficiently on LB agar, albeit less rapidly than strain 3610.…”
Section: Discussionmentioning
confidence: 99%
“…Such patterns also occur in the branching architecture of the lung and in structures formed by non-living systems, for example snow crystals. Swarming in B. subtilis is reported to require the presence of flagella (Ohgiwari et al, 1992), although flagellaindependent swarming has also been described recently (Kinsinger et al, 2003). An antibiotic surfactant, whose synthesis is subject to control by quorum sensing (Solomon et al, 1995;Solomon & Grossman, 1996), has also been implicated in swarming in this organism (Kearns & Losick, 2003;Bees et al, 2000; see also Wakita et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It consists of a cyclic heptapeptide moiety with the typical sequence GluLeu-D-Leu-Val-Asp-D-Leu-Leu which is closed to a lactone ring by a C 14-15 b-hydroxy fatty acid. Surfactin is highly surface active, which may play a key role for the motility of the bacillus (Kinsinger et al 2003) as well as for technical applications (Cameotra and Makkar 2004). Given the great interest in the development of new peptide antibiotics, it is of particular relevance that surfactin possesses also hemolytic (Kracht et al 1999), anti-viral (Kracht et al 1999;Vollenbroich et al 1997a), anti-bacterial (Beven and Wroblewski 1997;Vollenbroich et al 1997b), and anti-tumor (Kameda et al 1974) activity.…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria synthesize biosurfactants (1). Marangoni flows driven by surface-tension gradients can account for the flagellar-independent colony expansion of some species, such as Bacillus subtilis that produces surfactin (12)(13)(14). However, this cannot be the general mechanism driving swarm-fluid spreading because most swarming is flagella dependent and does not always require production of surfactants (1).…”
mentioning
confidence: 99%